Post renal transplant polycythemia and treatment- single center study - Azhar Ali Khan; Haroon Ayub; Waqar Ahmed; Azhar Waheed Khan (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To calculate the incidence of post-transplant erythrocytosis, and to assess the response to treatment. Method: The prospective study was conducted from April 2016 to April 2018 at the Department of Nephrology, Bahria International Hospital, Lahore, Pakistan, and comprised patients undergoing renal transplantation who were evaluated and followed up for 12 months. Patients having haemoglobin levels ?17gm/dl were labelled as having polycythemia. Data was analysed using SPSS 21. Results: Of the 94 total patients, 69(73.4%) were enrolled. During follow-up, 2(2.9%) of them died, and, thus, the final sample stood at 67(71.3%); 57 (85%) males and 10(15%) females. The mean age of the sample was 32.6±8.8 years. Overall, 19(28.4%) patients developed polycythemia and they were either given angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers. Of these 19 patients, 11(57.8 %) responded to the treatment, while 8(42.1%) required phlebotomy. Further, 3(15.7%) patients required one phlebotomy, while 5(26.3%) who had glomerular filtration rate >30% had to have repeated phlebotomy. Conclusion: The incidence of post-transplant erythrocytosis was significantly high at 28.4%. Key Words: Post-transplant polycythemia, Erythrocytosis, Continuous...